Perioperatory antibiotic prophylaxis in Pediatric Surgery (Part I: abdominal surgery) - Sergio Luis González López; Luis Marcano Sanz; Rafael Trinchet Soler; Zoe Quintero Delgado; Carlos Cabrera Machado; Lorenzo Pérez Romano; Guillermo Cortiza Orbe; Berta Fonseca Romero (Medisur)
The surgical wound infection is the biggest cause of infectious morbility in surgical patients. It is an important cause of morbility that causes lincreased hospital demurrages, increased cost of medical attention and serious inconveniences to the patients and their familiies. 25% of all nosocomial infections are surgical wound infection. One of the big advances of the surgery in the last three decades is an introduction of antibiotic prophylaxis in the surgical practice. Is considered that it has saved more lives than any other novel procedure in surgery in the last 20 years. We presented the Good Clinical Practices Guideline for Antibiotic prophylaxis in abdominal surgery, approved by consensus in the 1st National Good Clinical Practices Workshop in Pediatric Surgery (Cienfuegos, Cuba, March 7 – 9, 2002).